The analytic expressions of sensitivity parameters for fiber-optic refiective system - Kleiza, Vytautas; Verkelis, Jonas (Lietuvos matematikos rinkinys, 2004)
In this work the analytic expressions of absolute maxima and envelope for family of signals curves have found, which are more accurate than experimental data.